(untitled) (Journal of Technology and Operations Management, 2024)
Background/Aim- Intellectual Property valuation refers to the valuation of property rights for creations of the mind such as patent, trademark and copyright. The selection of valuation approach for Intellectual Property is often difficult as there is a lack of availability of information for this sector. However, there is inconsistency in the recognition and measurement of Intellectual Property. Moreover, valuation practice is always subject to the appraisers’ subjectivity. Thus, the purpose of this paper is to identify the criteria for the practice in conducting valuation for Intellectual Property. The data collection by using semistructured interview was adopted with the certified Intellectual Property valuers who were experienced in the practice of Intellectual Property valuation and been analysed using thematic data analysis. This paper identified the elements for Intellectual Property valuation as practiced by the Malaysian certified Intellectual Property valuers. The findings are beneficial to practitioners in Intellectual Property valuation as well as policy makers in Malaysia Intellectual Property industry.